Sanitasi Lingkungan Rumah Penderita TB Paru - Barus, Linda; Masra, Ferizal; Indarwati, Suami (MIDWIFERY JOURNAL, 2024)
Background: Tuberculosis (TB) is an infectious disease caused by infection with the Mycobacterium Tuberculosis bacteria. This disease can spread through droplets from people who have been infected with TB bacilli. Pulmonary tuberculosis is a direct infectious disease caused by the bacterium Mycobacterium Tuberculosis. Most TB germs attack the lungs but also affect other body organs.Purpose: The aim of the research is to determine the relationship between home environmental factors and the incidence of pulmonary tuberculosis in the work area of the Bogatama Health Center, Tulang Bawang Regency.Methods: This type of research is descriptive research, because it will describe the sanitary conditions of the home environment of pulmonary TB sufferers in the working area of the Bogatama Community Health Center, Tulang Bawang Regency, Lampung Province.  The population is 25 houses and the sample is the total population, this research is all the houses of pulmonary TB sufferers who were registered for treatment at the Bogatama Community Health Center, Tulang Bawang Regency, Lampung Province during 2023, 25 houses and 25 houses that were not pulmonary TB sufferers as controls. (Report of the Bogatama Health Center, Tulang Bawang Regency, 2023). The research location was carried out in the work area of the Bogatama Community Health Center, Tulang Bawang Regency, Lampung Province in July-November 2024.Results: The results of the research obtained data that there was no relationship between the type of floor and the incidence of pulmonary tuberculosis in the working area of the Bogatama Community Health Center with a p value of 0.185. There was a relationship between lighting intensity and the incidence of pulmonary tuberculosis in the working area of the Bogatama Community Health Center with a p value of 0.046. There was a relationship between humidity and the incidence of tuberculosis. Lungs in the Bogatama Community Health Center working area with a p value of 0.048, there is a relationship between ventilation area and the incidence of pulmonary tuberculosis in Bogatama Community Health Center working area with a p value of 0.001. There is a relationship between residential density and the incidence of Pulmonary Tuberculosis in the Bogatama Community Health Center working area with a value.Conclusion: There is no relationship between floor type and the incidence of pulmonary tuberculosis in the working area of the Bogatama Community Health Center, but there is a relationship between lighting intensity, humidity, ventilation area, and occupancy density and the incidence of pulmonary tuberculosis in the working area of the Bogatama Community Health Center, Tulang Bawang Regency.Suggestion: For Bogatama Community Health Center Health Officers to improve environmental health services in order to reduce the incidence of Pulmonary Tuberculosis, it is necessary to empower the community including providing outreach to families regarding education about environmental-based diseases, as well as playing a major role in education by using the sanitation clinic services available at the community health center. Sanitation clinics at community health centers play a role as counseling, inspection and environmental sanitation interventions which will reduce the incidence of pulmonary tuberculosis. The community should also always pay attention to the condition of the home environment, including information about members of the community experiencing signs and symptoms of Tuberculosis, so that Tuberculosis patients can be detected and treatment can be carried out immediately. Keywords: Sanitation, Home Environment, Pulmonary TB